Position of maximal nasopharyngeal maximal occlusion in relation to hamuli pterygoidei: use of hamuli pterygoidei as landmarks for palatoplasty in brachycephalic airway obstruction syndrome surgical treatment. (22nd July 2018) - Sarran, D.; Caron, A.; Testault, I.; Segond, S.; Billet, J. P.
Abstract : Objectives: To assess the influence of complete nasopharyngeal occlusion on respiratory signs in brachycephalic dogs. To determine the cranio‐caudal position of rostral nasopharyngeal occlusion in relation to the hamuli pterygoidei in brachycephalic dogs. To determine whether using the hamuli pterygoidei as anatomical landmarks for palatoplasty results in clinical respiratory improvement. Materials and Methods: Prospective study of dogs diagnosed with brachycephalic obstructive airway syndrome. The dogs were scored according to the severity of their clinical respiratory signs and the nasopharynx was CT scanned. The site of most rostral nasopharyngeal occlusion was measured in relation to the hamuli pterygoidei . Measurements were compared between brachycephalic obstructive airway syndrome group, completely occluded and partially occluded groups. The hamuli pterygoidei were used as the most cranial landmarks for the palatoplasty incision, such that the incision was made at the point of maximal nasopharyngeal occlusion. Owners were interviewed by telephone for the medium‐term follow‐up. Results: Thirty‐five dogs were included. There was no significant association between the severity of respiratory clinical signs and extent of nasopharyngeal occlusion. Maximal nasopharyngeal occlusion was always located directly caudal to the hamuli pterygoidei (mean ±sd value of 9∙4 ±6∙5 mm). hamuli pterygoidei were easily palpable perioperatively in all cases. There was a significant improvement of clinical grades postoperatively. Clinical Significance: The hamuli pterygoidei are a reliable landmark for soft palate incision for palatoplasty in these cases but the distance between them and the site of maximal nasopharyngeal occlusion varied greatly.